Fisheries Reference Points under Varying Stock Productivity and Discounting: European Anchovy as a Case Study - TUNCA, SEZGIN; LINDROOS, MΑRKO; LINDEGREN, MARTIN (Mediterranean Marine Science, 2022)
European anchovy (Engraulis encrasicolus) is the main commercially exploited fish stock in the Black Sea region, providing a vital source of livelihood and revenue for local communities and national economies. In recent decades, the Black Sea anchovy stock has faced many human-induced threats, including overfishing, eutrophication, invasive species, and climate change while these threats have raised concerns about the status and long-term productivity of the stock. To ensure sustainable levels of exploitation under potential future changes in stock productivity, we here estimate and compare a suite of biological and economic reference points under different levels of stock productivity and discount rates using an age-structured bioeconomic model setup. Our model simulations showed that optimal fishing mortalities achieving maximum sustainable yield (FMSY) and maximum economic yield (FMEY) increase at higher stock productivity but are always lower than the historically high mean levels of exploitation. Furthermore, we illustrate that the stock biomass at maximum economic yield (BMEY) is larger than the stock biomass at maximum sustainable yield (BMSY) at all stock productivities and discount rates, except at low stock productivity under high levels of discounting (i.e., 10%, 20%). By illustrating the ecological and economic benefits of reducing exploitation rates, we expect that our estimated reference points can add value to the decision-making process for the management of the European anchovy fishery and ensure long-term sustainable management even under future climate-driven changes in stock productivity.